The use of fast acting antioxidants for the reduction of cow placental retention and subsequent endometritis - KUMAR, HARENDRA; MAHMOOD, S (The Indian Journal of Animal Sciences, 2014)
Vitamin E either with selenium or vito A as antioxidants was administered to reduce incidence of retained placenta and uterine infections that could delay subsequent conception. Pregnant multiparous crossbred cows (70) were grouped into 3: animals in group 1 (n=30) injected with 400 mg vil. E and 121akh IU vito A, group 2 (n=20) with 500 mg vit. E and 15 mg selenium at 4 weeks before expected calving and group 3 (n=20) an untreated control. The serum levels of different biochemical parameters were also estimated at prepartum stage. These animals were observed for occurrence of placental retention following parturition. The placental retention 24hr after parturition was 25% in control and reduced to 10 and 15% in treated groups 1 and 2 respectively. Endometritis occurred in 100% of the animals following placental retention as compared to 10.17 % of those with normal expUlsion of the fetal membranes. A comparison of reproductive indices showed no significant improvement in fertility of treated cows. The results revealed that serum levels of alkaline phosphatase and progesterone, were higher at 250 Â± 10 days of gestation in cows which experienced placental retention following calving.